Optimization of comprehensive two-dimensional gradient chromatography coupling in-line hydrophilic interaction and reversed phase liquid chromatography - Jandera, Pavel; Hájek, Tomáš; Staňková, Magda; Vyňuchalová, Kateřina; Česla, Petr (Journal of chromatography. A, 2012)
In-line coupled comprehensive HILIC×RP systems should offer larger selectivity differences and better two-dimensional orthogonality than coupled RP×RP systems. However, this may not apply for all systems. The HILIC selectivity depends on the mix of selective polar and non-polar interactions with the functional groups, but also with the matrix of polar columns and depends on the sample type. We synthesized a new polar monolithic sulfobetaine polymethacrylate capillary column with excellent efficiency for low-molecular compounds. When used in the first, HILIC dimension coupled to core-shell or monolithic RP columns in the second dimension, this column provides much improved orthogonality for two-dimensional separations of phenolic and flavonoid compounds, in comparison to silica-bonded Diol, Polyethylene glycol or Zwitterionic columns. We investigated the performance of 11 short 5 cm and 3 cm columns for fast (1-2 min) gradient second-dimension separations. Band broadening or distortion may occur in directly coupled comprehensive HILIC×RP systems, due to strong solvent-strength differences between the mobile phases used in the first and in the second dimension. To suppress this effect, low fraction volumes were collected from a 0.5mm I.D. capillary monolithic sulfobetaine column at the flow-rate of a few microliters per min, coupled in-line with various core-shell columns operated at the maximum flow-rate. This setup with simultaneous gradient elution in the HILIC and in the RP dimension provided successful separation of natural antioxidants.
Keywords: Chromatography, High Pressure Liquid; flavonoidy; antioxidancia; chromatografie s reverzní fází; vysokoúčinná kapalinová chromatografie; Flavonoids; Hydrophobic and Hydrophilic Interactions; Antioxidants; hydrofobní a hydrofilní interakce; Phenols; fenoly; Chromatography, Reverse-Phase